Direct reductive amination of ketones with amines by reductive aminases - Bo-Bo Li (KeAi Communications Co. Ltd., 2021)
Direct reductive amination of ketones by reductive aminases (RedAms) is a promising method for the synthesis of primary, secondary and tertiary amines. In this work, five naturally occurring RedAms possessing reductive amination activity were identified using a structure-guided genome mining (SGGM) approach, which was based on highly conserved substrate binding and catalysis motif alignment. This RedAm toolbox facilitated the reductive amination of cyclohexanone and 4-fluoropropiophenone with various amine nucleophiles. In a preparative biotransformation (100 ​mg) with low stoichiometric ammonia donor and low catalyst loading, and three types of N-alkylcyclohexylamine were efficiently synthesized with a space-time yield up to 64.2 ​g ​L−1 ​d−1, demonstrating the potential of the RedAm enzymes as a biocatalyst toolbox for the synthesis of primary and secondary amines. Additionally, through protein engineering, the W205F variant of KfRedAm from Kribbella flavida was obtained with a 2-fold increased catalytic efficiency (kcat/Km), and the general applicability of the variant was verified, providing useful guidance for further evolution of RedAms within this family.